The Representation of Social Discrimination in Kiera Cass’ The Selection - Aura Leilashafa Dibhan; Dina Dyah Kusumayanti; Itsna Syahadatud Dinurriyah (Pusat Studi Gender Universitas Jember, 2023)
Social discrimination is a never-ending issue that happens not only in reality but also in fiction novels. It is described as perpetual inequality of people based on their disability, illness, sexual orientation, religion, or any other. Hence, literature as a cultural product has a potential to deliver social discrimination discourse. This research aims to discuss how the social discrimination depicted in Kiera Cass’ The Selection. The Selection is a story about an event to find a prince’s bride in Illéa. The caste system and absolute monarchy exist in Illéa’s kingdom. Depending on their jobs, people are divided into eight castes. In this research, the representation theory by Stuart Hall is applied. The study’s analysis is qualitative with the novel as primary data and other supporting sources as secondary data. The collected data are used to indicate how social discrimination between castes constructed in the novel, how it is related to the condition in the United States of America in 1900s, and where the author took a side with. The result of the research shows that social discrimination occurs as the absolute position of the caste and it is difficult to change this situation. The novel’s social discrimination is also related to the real condition of the United States of America in the early 1900s, which includes job, partner, and lifestyle aspects. The author appeared to position herself more on the side of the lower caste at first, but no solution is offered as a result of the lower caste’s work.